Blockchain based secure energy marketplace scheme to motivate peer to peer microgrids - Muhammad Awais; Qamar Abbas; Shehbaz Tariq; Sayyaf Haider Warraich (Institute of Advanced Engineering and Science, 2022)
In the past few years, the trend of microgrids has been increasing very fast to reduce peak-hour costs. However, in these systems, third parties are still involved in selling surplus energy. This raises the cost of energy, and such systems have numerous operational and security barriers. These issues can be solved by the decentralized distributed system of microgrids, where a consumer can locally sell their surplus energy to another consumer. To deploy such a system, one must consider security barriers for the transaction of energy. This paper proposes a solution to these problems by devising a scheme as a marketplace where users interact with each other to buy and sell energy at better rates and get energy-generating resources on lease so that users do not have to worry about capital investment. An agreement between the owner of resources and the consumer is recorded on blockchain-based smart contracts. In this paper, a survey of well-known decentralized energy solutions is conducted. This paper also proposes an extra layer of security to leverage a shielded execution environment so that information about energy generated, utilized, and shared cannot be changed by consumers and third parties even if the system is compromised.